Terminus Positions and Flowlines of Vincennes Bay Outlet Glaciers, East Antarctica, 1963-2022 ... - Picton, Hannah; Stokes, Chris; Jamieson, Stewart (NERC EDS UK Polar Data Centre, 2023)
The dataset contains terminus positions and flowlines of the Vincennes Bay Outlet Glaciers, for the years 1963-2022. These are provided as shapefiles, associated with a paper submitted to The Cryosphere entitled Extensive and anomalous grounding line retreat at Vanderford Glacier, Vincennes Bay, Wilkes Land, East Antarctica (Picton et al., 2023). The dataset is divided into three separate folders: (i) flowlines, (ii) sampling boxes, and (iii) terminus positions. The flowlines and sampling boxes, shown in Figure 1B (Picton et al., 2023), were used to facilitate data collection. The terminus positions represent annual terminus positions manually digitised from satellite imagery. Flowlines, sampling boxes and terminus positions are provided for each of the Vincennes Bay outlet glaciers: Vanderford, Adams, Anzac, Bond East, Bond West, and Underwood. Chris Stokes and Stewart Jamieson acknowledge funding from the UK Natural Environment Research Council grant NE/R000824/1. ... : All shapefiles were manually digitised within QGIS. Terminus positions were manually digitised from KH-5 ARGON (Kim et al., 2007), Landsat-1, Landsat-4, Landsat-5, Landsat-7, Landsat-8, Sentinel 2A and Sentinel-2B imagery (1963-2022). Picton et al. (2022) provide details of each satellite scene ID used within the supplementary material. Picton et al. (2022) uses grounding-line positions from Vincennes Bay derived using differential synthetic aperture radar interferometry (DInSAR). This dataset can be found at the ENVEO cryoportal (cryoportal.enveo.at), entitled GLL, Vincennes Bay, Antarctica, 1996 - 2020. Vincennes Bay is defined as the shelf region situated on the Wilkes Land coast between 104° E and 111° E (Ribeiro et al., 2021). Vincennes Bay overlies the Aurora Subglacial Basin and is drained by several marine-terminating outlet glaciers: Vanderford, Adams, Anzac, Bond, and Underwood. ...